Physism of Roland Omnés - unity of the worlds of mathematics and physics; Part I - Quantum problems of abstraction - Grygiel, Wojciech (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2008)
Inasmuch as mathematical platonism can be clearly matched with the radical realism, there exists a possibility to point out an approach, promoted by a French physicist, Roland Omnés, that is equivalent to the Aristotelian position of moderate realism. This standpoint denies the existence of an independent universum of mathematical entities and claims that mathematics is encoded in the laws of physics. In analogy to logicism, where mathematics is considered to be reducible to logic, Omnés' position is called by him 'physism' to stress the reducibility of mathematics to the laws of physics. The goal of Roland Omnés is to construct a common philosophy of mathematics and physics where the realities of these two disciplines converge. The first part of the analysis aims at the description and critical evaluation of physism from the point of view of the adequacy of the consistent histories interpretation of quantum mechanics to provide physical basis of the abstraction of the mathematical structures from the physical reality.